Improving function in people with hip-related pain: a systematic review and meta-analysis of physiotherapist-led interventions for hip-related pain. Issue 23 (6th May 2020) - Kemp, Joanne L; Mosler, Andrea B; Hart, Harvi; Bizzini, Mario; Chang, Steven; Scholes, Mark J; Semciw, Adam I; Crossley, Kay M
Abstract : Objective: To report the effectiveness of physiotherapist-led interventions in improving pain and function in young and middle-aged adults with hip-related pain. Design: Systematic review and meta-analysis. Data sources: A comprehensive, reproducible search strategy was performed on five databases in May 2019. Reference lists and grey literature were also searched. Eligibility criteria for selecting studies: Population: people aged ≥18 years with hip-related pain (with or without a diagnosis of femoroacetabular impingement syndrome). Intervention(s): physiotherapist-led interventions for hip pain. Comparators: sham treatment, no treatment or other treatment (eg, hip arthroscopic surgery). Outcomes: primary outcomes included patient-reported hip pain and function. Secondary outcomes included physical function measures. Results: 1722 papers were identified. After exclusion criteria were applied, 14 studies were included for analysis. They had varied risk of bias. There were no full-scale placebo-controlled randomised controlled trials (RCTs) of physiotherapist-led treatment. Pooled effects ranged from moderate effects (0.67 (95% CI 0.07 to 1.26)) favouring physiotherapist-led intervention over no treatment post-arthroscopy, to weak effects (−0.32 (95% CI 0.57 to 0.07)) favouring hip arthroscopy over physiotherapist-led treatment. Conclusion: Physiotherapist-led interventions might improve pain and function in young and middle-aged adults with hip-related pain, however full-scale high-quality RCT studies are required. PROSPERO registration number: CRD42018089088.